Determinan Stunting Anak Usia 0-2 Tahun Di Indonesia: Bukti Survei Cross Sectional Menunjukkan Peran Penting Pemberian Tablet Tambah Darah Pada Ibu Hamil Dalam Penurunan Stunting - Nina Fentiana; Daniel Ginting (Jurnal Ventilator, 2023)
There has been a shift in the age group of stunting children between 2018-2019 in Indonesia. The decline in the prevalence of stunting occurred in the younger age group, namely 0-5 months, 6-11 months and 12-23 months. This study aims to analyze the determinants of stunting in children aged 0-2 years in Indonesia based on cross-sectional survey evidence. This research is a retrospective study to get an overview of the incidence of stunting in children 0-23 months in Indonesia in 2013 as a basis for seeing the achievement of reducing stunting. The research analyzed secondary data from the 2013 Basic Health Research which measured 27,779 heights of children 0-2 years in 33 provinces in Indonesia. The results showed that a history of giving iron tablets to pregnant women was the factor most related to the incidence of stunting in children 0-2 years in Indonesia. The program to accelerate the reduction of stunting in Indonesia in 2024 to 14% needs to consider increasing the coverage of iron supplement administration to pregnant women and women of childbearing age..